2014
DOI: 10.1177/2049463714545136
|View full text |Cite
|
Sign up to set email alerts
|

Cancer pain physiology

Abstract: Mechanisms of inflammatory and neuropathic pains have been elucidated and translated to patient care by the use of animal models of these pain states. Cancer pain has lagged behind since early animal models of cancer-induced bone pain were based on the systemic injection of carcinoma cells. This precluded systematic investigation of specific neuronal and pharmacological alterations that occur in cancer-induced bone pain. In 1999, Schwei et al. described a murine model of cancer-induced bone pain that parallele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 75 publications
0
42
0
7
Order By: Relevance
“…The most common cause of cancer-induced pain arises from bone metastases. [1] Of advanced cancer suffers, 60–84% are estimated to experience varying degrees of bone pain. [2] Cancer-induced bone pain (CIBP) involves both neuropathic and inflammatory pain pathways, associated with tumor, stroma, and adjacent tissues, including peripheral and central nerves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common cause of cancer-induced pain arises from bone metastases. [1] Of advanced cancer suffers, 60–84% are estimated to experience varying degrees of bone pain. [2] Cancer-induced bone pain (CIBP) involves both neuropathic and inflammatory pain pathways, associated with tumor, stroma, and adjacent tissues, including peripheral and central nerves.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Cancer-induced bone pain (CIBP) involves both neuropathic and inflammatory pain pathways, associated with tumor, stroma, and adjacent tissues, including peripheral and central nerves. [1]…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the development of inflammation, neuropathic changes have also been reported in animal models of bone and joint pain [67, 68, 47, 69, 70]. Studies in rat and mouse models of cancer-induced bone pain and chemical-induced osteoarthritis joint pain have demonstrated expression of ATF3, a neural marker of nerve damage, in cell bodies within the dorsal root ganglion innervating the bone or joint [71–73, 69].…”
Section: Site Of Injury or Pathologymentioning
confidence: 99%
“…Many animal and clinical studies have demonstrated that sensitization of peripheral and central neurons develops in the context of chronic bone or joint pain [5, 67, 78]. The international association for the study of pain (IASP) defines sensitization as “Increased responsiveness of nociceptive neurons to their normal input, and/or recruitment of a response to normally subthreshold inputs”.…”
Section: Sensitizationmentioning
confidence: 99%
See 1 more Smart Citation